2021
DOI: 10.1080/15230406.2021.1929492
|View full text |Cite
|
Sign up to set email alerts
|

Embodied gesture interaction for immersive maps

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
3

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…From our iterative gesture refinement in VR, we draw insights beyond prior research [4,[9][10][11][12]: (1) Natural finger movements yield superior results compared to unnatural counterparts. The "scissor" gesture garnered negative feedback due to reported fatigue and discomfort, whereas gestures like "crumpling" and "flicking" received no such complaints, as their finger movements felt more natural;…”
Section: Observations and Discussionmentioning
confidence: 99%
“…From our iterative gesture refinement in VR, we draw insights beyond prior research [4,[9][10][11][12]: (1) Natural finger movements yield superior results compared to unnatural counterparts. The "scissor" gesture garnered negative feedback due to reported fatigue and discomfort, whereas gestures like "crumpling" and "flicking" received no such complaints, as their finger movements felt more natural;…”
Section: Observations and Discussionmentioning
confidence: 99%
“…Research has demonstrated the role of immersion for data analysis and sensemaking, such as the possibility of unlimited screen space [4,32,46,61], effects on spatial memory [58], 3D spatial interaction [10,53,62], collaboration [45,65,67], engagement [9,19,20,49,54], and entertainment [9,78]. Immersive analytics scenarios can be implemented in a variety of contexts, ranging from handheld mobile devices providing e.g., see-through augmented reality, to head-worn devices or caves [7,10].…”
Section: Immersive Analytics and Embodied Interactionmentioning
confidence: 99%
“…We aim to increase our understanding of the benefts of Immersive Analytics applications, for instance A) using space around the user to support visual analytics; B) spatial layouts of immersive small multiples; C) using tangible interfaces to support collaborative embodied interaction; or D) using hands to enhance comprehension of data physicalisations. 14,19,24], spatial memory [23], proprioception, 3D spatial interaction [21,25], tangible interaction [7,13,28,29], collaboration [18,26], kinesthesia, engagement [5,6], etc. While evidence of these benefts has been accumulating even prior to the establishment of Immersive Analytics, we have still attained only a basic understanding of the extent to which they can support human sensemaking, and reliance on such assumptions is prevalent in the exploration of applications.…”
Section: Introductionmentioning
confidence: 99%